Ecosophy as an Epistemological Proposal of Ecofeminist Theology in the Latin American Context - Rojas Salazar, Marilú (2011)
The proposal of ecofeminist theology tries to give answers to the questions posed by the hermeneutics of gender and ecology regarding knowledge: how is it that we know, and where is it that we place ourselves in order to know? How can we experience this criterion of truth in the daily life of poor women of the ‘third world’? How is it that a ‘certain form of knowledge’ has been used as an instrument of domination and exclusion of women and the ecosystems? The answer proposed by ecofeminist theology is ecosophy (the wisdom of the oikós). Ecosophy is a form of knowledge derived from the experience of ancestral Mesoamerican indigenous peoples, which is based upon equilibrium, fl uidity, integration of the senses, and corporality. These elements are proposed as the starting point for the reflection of the ecofeminist theology, ethics, and spirituality. Ecosophy is characterised by being relational, inclusive, starting from corporal experience, integrating affectivity, and by being sustained in interdependence and interconnectivity. It is not only a ‘traditional wisdom’ but it is also an epistemological basis that can reconstruct symbols and rites in a different way from Western logic: 1) It deconstructs the epistemological model that make an understanding of human knowledge as masculine possible; 2) it deconstructs the knowledge that makes a centralising monotheism possible; 3) it upholds the immanence of God from a panentheistic theological reflection. Ecosophy is a holistic and inclusive theological line that emerges from the experience of a faith of daily life for daily life.